Fabrication of hollow mesoporous silica-based nanoreactors for enzyme immobilization: high loading capacity, effective protection, and recyclability. (January 2023) - Zhang, Yipin; Qi, Chenyang; Tu, Jing
Abstract: The poor stability and low reusability of enzymes have always been the hindrances to their large-scale applications. Herein, hollow mesoporous silica (HMS) nanoparticles have been constructed as nanoreactors for in situ enzyme immobilization, hemoglobin (Hb) was selected as a model enzyme. By utilizing zeolitic imidazolate framework-8 (ZIF-8) as the sacrificial template, the synthesis mechanism of Hb@ZIF-8 has been explored by adjusting the molar ratios of Zn 2+ and 2-methylimidazole. When the amount of Hb was constant, the shape of Hb@ZIF-8 gradually changed from flake to granular (from 50:200 mM to 50:800 mM). Furthermore, when the molar ratio of Zn 2+ and 2-methylimidazole was fixed, with the amount of Hb increasing, the size of Hb@ZIF-8 decreased gradually, with maximum loading capacity of 460 μg/mg. Subsequently, Hb@ZIF-8 was coated with silica shells and followed by the removal of ZIF-8 in phosphate-buffered saline (pH 5), resulting in Hb@HMS. Compared to free Hb, Hb in HMS nanoreactors maintained over 74% of original catalytic activity under extreme conditions, showing significant improvements on the stability. Further, Hb@HMS still retains 80% of enzymatic activity after 5 cycles, exhibiting its excellent reusability. This work provides an efficient strategy for enzyme immobilization, giving new horizons for biosensing, biocatalysis and biomedicine. Graphical abstract: Hollow mesoporous silica-based nanoreactors with high loading capacity of hemoglobin. Image 1 Highlights: Size-controllable hemoglobin (Hb) encapsulated in zeolitic imidazolate framework-8 particle can be achieved. The loading capacity of Hb was more than 460 μg/mg in hollow mesoporous silica nanoreactors. Hb in hollow mesoporous silica nanoreactors maintains over 74% of enzymatic activity under extreme conditions.